Labor environment at Universidad del Valle de Puebla, Campus Tehuacan An analysis of outcome measurment - Benavides Camarillo, Angel (2020)
Organizations are a place where a culture of behavior and development of individuals (collaborators) is lived  and created. In an educational organization, situations are especially observed both by members of the  infrastructure and by the community being served. The analysis of these features allows us to know, in a  deeper way, what are the reasons for a work atmosphere and the opportunity areas that a company presents  in the correct management of human capital. This paper reports the ﬁndings of the research regarding the  work environment at the Universidad del Valle de Puebla, Plantel Tehuacán, which aims to provide an  overview of the characteristics of administrative staﬀ and the factors (physical, mental, emotional,  professional, technological and managerial) that inﬂuence their performance. From this, it can be inferred  that, despite the permeability of these in the professional performance, there is a harmonic scenario that  favors the performance and the attention to the users of the educational service, in accordance with the  institutional vision and mission.